An information-motivation-behavioral skills model of adherence to antiretroviral therapy. - Fisher, Jeffrey D; Fisher, William A; Amico, K Rivet; Harman, Jennifer J (Health psychology : official journal of the Division of Health Psychology, American Psychological Association, 2006)
HIV-positive persons who do not maintain consistently high levels of adherence to often complex and toxic highly active antiretroviral therapy (HAART) regimens may experience therapeutic failure and deterioration of health status and may develop multidrug-resistant HIV that can be transmitted to uninfected others. The current analysis conceptualizes social and psychological determinants of adherence to HAART among HIV-positive individuals. The authors propose an information-motivation-behavioral skills (IMB) model of HAART adherence that assumes that adherence-related information, motivation, and behavioral skills are fundamental determinants of adherence to HAART. According to the model, adherence-related information and motivation work through adherence-related behavioral skills to affect adherence to HAART. Empirical support for the IMB model of adherence is presented, and its application in adherence-promotion intervention efforts is discussed.
Keywords: Anti-Retroviral Agents; Empirical Research; Health Behavior; HIV Infections; Humans; Information Dissemination; Motivation; Patient Compliance; Psychology